2012
DOI: 10.1002/bab.1049
|View full text |Cite
|
Sign up to set email alerts
|

Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.)

Abstract: Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Here, we show the change in the colour of the root to light brown colour. In earlier reports in A. hypogaea (peanut) (Raju et al 2012) and Sesbania too, the colour of roots changed to purple when they synthesized intracellular gold nanoparticles and also confirmed the presence of intracellular nanoparticles (Sharma et al 2007). …”
Section: Visible Analysissupporting
confidence: 60%
See 3 more Smart Citations
“…Here, we show the change in the colour of the root to light brown colour. In earlier reports in A. hypogaea (peanut) (Raju et al 2012) and Sesbania too, the colour of roots changed to purple when they synthesized intracellular gold nanoparticles and also confirmed the presence of intracellular nanoparticles (Sharma et al 2007). …”
Section: Visible Analysissupporting
confidence: 60%
“…In previous report, the synthesis of gold nanoparticles with living peanut seedling has been demonstrated, where it was suggested that some of the proteins and phenolics leached from the roots helped in the formation of GNPs (Raju et al 2012). Possibly these factors might have played role in the reduction of silver nanoparticles also.…”
Section: Shapes and Sizes Of Nanoparticlesmentioning
confidence: 95%
See 2 more Smart Citations
“…These methods are considered more cost-effective, safe, and eco-friendly [7]. In addition, they require ambient conditions like room temperature, atmospheric pressure, and physiological pH [8]. Among biological systems, living plants are renewable, safe to handle and easily available resources for nanoparticle production [1].…”
Section: Introductionmentioning
confidence: 99%